Evaluasi Usability pada Aplikasi Identitas Kependudukan Digital (IKD) Menggunakan System Usability Testing - Faridatus Sholikhah; Mochammad Anshori; M. Syauqi Haris (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
This study aims to evaluate the usability of the Digital Population Identity (Identitas Kependudukan Digital/IKD) application using the System Usability Scale (SUS) method. A descriptive quantitative approach was employed, with the study conducted at the Department of Population and Civil Registration (Disdukcapil) of Malang City. Data were collected through a Google Forms-based SUS questionnaire distributed to 50 respondents selected using purposive sampling, consisting of users with prior experience using the IKD application. The research instrument comprised 10 SUS statements measured on a five-point Likert scale. The validity test indicated that all questionnaire items were valid with r-values exceeding 0.2732, while the reliability test produced a Cronbach's Alpha value of 0.834, indicating good internal consistency. The SUS evaluation yielded an average score of 77.42, categorized as Acceptable, achieving Grade B with a Good adjective rating. However, the Net Promoter Score (NPS) remained in the Passive category, indicating the need for improvements in data integration stability and facial registration procedures to enhance user satisfaction and encourage stronger user advocacy.